ECOLOGICAL INDICES OF PARASITES OF SCARTICHTHYS GIGAS (STEINDACHNER, 1876) (PERCIFORMES: BLENNIIDAE) OF THE COASTS OF LIMA, PERU - Iannacone, José (2012)
The giant blenny, Scartichthys gigas (Steindachner, 1876) (Blenniidae), is endemic to the eastern South Pacific and abundant in rocky intertidal environments. We investigated some ecological indices of the parasitefauna of 72 S. gigas acquired at Fishing Terminal from Chorrillos, Lima, Peru fromSeptember 2008 to August 2009. Fish were necropsied to census helminth and crustacean parasites. Four species of parasites were found with the following prevalence and mean abundance,respectively: an isopod, Ceratothoa gaudichaudii (H. Milne Edwards, 1840) (1.4% and 0.01), a copepod, Acanthocondria syciasis (Kroyer, 1863) (55.6 and 1.56), a digenean, Zoogonus rubellus (Olson, 1868) (26.4% and 0.26), a nematode, Johnstonmawsonia sp., (6.9 % and 0.17). Only linear correlation was observed between the size of host fish, and the prevalence and total abundance of Z. rubellus. Similarly, the size was found to be related to the number of parasite species of S. gigas. We found no dependence between the sex of S. gigas and mean abundance and prevalence of infection of the most prevalent parasites. Analysis of eight indices of aggregation: Z. rubellus showed that three indexes showed a random distribution (Dispersion, Morisita standardized and Discrepancy of Poulin), four uniforms (Morisita, Green, average aggregation of Lloyd and patchiness) and the binomial coefficient K without a specific pattern. Divergences in the type of distribution were found depending on the index used. In contrast in A. syciasis, eight aggregation indices indicated an aggregated distribution and total congruence with each other. The diversity of the parasite community component of S. gigas was H '= 0.31, Pielou index (J) = 0.50, the index of Simpson (C) = 0.62 and Berger-Parker index was 0.77.